Perlindungan Hukum terhadap Pihak yang Menjadi Korban Pembatalan Perkawinan Akibat Cacat Kehendak karena Penipuan dan Paksaan Berdasarkan Hukum Islam - Utari Sudrajat, Ayunda Ersa; Basani, Christin Septina (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2026)
This study examines the legal consequences of defective consent in marriage arising from fraud and coercion during the formation of the ijab kabul, as well as the forms of legal protection afforded to victims—particularly wives or female spouses—under Islamic law and Indonesian positive law. Using a normative juridical method and analysis of Law Number 1 of 1974, the Compilation of Islamic Law (KHI), the Civil Code, and the Kendari Religious Court Decision Number 0375/Pdt.G/2017/PA.Kdi, the research finds that fraud and coercion eliminate the element of free consent (ridha), which is a fundamental requirement for a valid marriage contract, thus allowing the marriage to be annulled by a final and binding court decision. Although the marriage is deemed never to have existed, the KHI ensures that children remain legitimate and that jointly acquired property is still legally recognized. Female victims receive specific legal protection, including rights to dowry, iddah maintenance, mut'ah, a portion of joint property, and the ability to claim material and immaterial damages resulting from fraud or coercion. Beyond legal remedies, women are also entitled to social protection such as counseling, psychological support, safe houses, and economic recovery assistance. These findings demonstrate a strong alignment between Islamic law and Indonesian positive law in upholding justice and providing comprehensive protection for women and children as the most vulnerable parties in marriage annulment cases caused by defective consent.